1991
DOI: 10.1177/096032719102300101
|View full text |Cite
|
Sign up to set email alerts
|

The effect on clinical judgements of new types of fluorescent lamp: I Experimental arrangements and clinical results

Abstract: Clinical studies were undertaken in hospitals to investigate the effects of various fluorescent lamps currently available on the colour appearance of skin by determining their influence on clinical diagnoses and judgements of perceived confidence in those decisions. The Department of Health were interested in the suitability of high-efficacy, narrow-band emitting lamps which offered savings in power and hence savings in revenue costs. A range of pathologies having different skin colour appearances were seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…This result is consistent with the United Kingdom Medical Research Council standard for fluorescent lighting in patient areas in hospitals: CCT around 4000 K and a high CRI (MRC [1965], cited in Lovett, Halstead, Hill, Palmer, Sonnex, and Pointer 1991). The initial recommendation was made following experimental trials using a variety of lamps ranging from 3000 K to 6500 K. A recent clinical trial of newly-developed lamps reiterated the earlier findings in that the fewest reported problems of colour appearance and difficulty of diagnosis occurred with lamps having colour temperatures around 4000 K and high CRI (Lovett et al 1991).…”
Section: Judgements Of Peoplementioning
confidence: 99%
“…This result is consistent with the United Kingdom Medical Research Council standard for fluorescent lighting in patient areas in hospitals: CCT around 4000 K and a high CRI (MRC [1965], cited in Lovett, Halstead, Hill, Palmer, Sonnex, and Pointer 1991). The initial recommendation was made following experimental trials using a variety of lamps ranging from 3000 K to 6500 K. A recent clinical trial of newly-developed lamps reiterated the earlier findings in that the fewest reported problems of colour appearance and difficulty of diagnosis occurred with lamps having colour temperatures around 4000 K and high CRI (Lovett et al 1991).…”
Section: Judgements Of Peoplementioning
confidence: 99%
“…[1][2][3][4][5][6][7] The effects of congenital red-green dichromasy have been represented in Figs. 3 and 4.…”
Section: Resultsmentioning
confidence: 99%
“…The selection of light sources for clinical observation has been the subject of a number of studies and standards, [1][2][3][4][5][6][7][8][9][10] although the earlier references [1][2][3] have been rendered obsolete by the changes in fluorescent tube technology and the standards written at the time 1,9 are similarly out dated. In particular, the change from halophosphate to triphosphor technology has dramatically changed lighting options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two images, the hue was altered as a decoy for the CVDs who might make decision on the basis of what looked normal or simply different from normal without regard to the nature of the difference. The white point of the monitor was set to approximate 4000 K, which is considered the "gold standard" for cyanosis observation [7,[11][12][13][14]. Twenty images were produced, see Fig.…”
Section: Methodsmentioning
confidence: 99%